The Costs and Benefits of Targeted Screening for Causes of Sudden Cardiac Death in Children and Adolescents - Leslie, Laurel K. (2012)
BACKGROUND: Sudden cardiac death (SCD) in children is a rare but devastating event. Experts have debated the merits of community-based screening programs utilizing an electrocardiogram (ECG) and targeting two potential high-risk groups: school-aged children initiating stimulant medications to treat attention deficit hyperactivity disorder (ADHD) and adolescents participating in sports. METHODS AND RESULTS: Simulation models incorporating detailed prevalence, sensitivity and specificity, and treatment algorithms were built to determine the cost-effectiveness of targeted SCD screening. Clinical care algorithms were constructed for asymptomatic children initiating stimulants for ADHD (age 8) or participating in sports (age 14) and presenting with a positive ECG finding suggestive of one of the three most common pediatric disorders causing SCD and identifiable by ECG. Information to develop simulation model assumptions was drawn from the existing literature, Medicaid fees, and expert judgment. Sensitivity analyses examined parameter ranges to identify influential sources of uncertainty. Outcomes included costs and lost life years (LYs) caused by condition-related mortality. Our models estimate that screening for all three conditions simultaneously would reduce sudden death risk by 3.6 to 7.5 × 10(−5) with projected life expectancy increases of 0.8–1.6 days per screened individual. The incremental cost-effectiveness of screening is $91,000 to $204,000 per LY. Sensitivity analysis showed that assumed disease prevalence, baseline mortality, and the relative risk of mortality due to stimulant medication use and sports participation had the greatest impact on estimated cost-effectiveness. CONCLUSIONS: Results based on assumptions favoring SCD screening indicated its cost is high relative to its health benefits.